Guerra commerciale USA-Cina: il vero ladro finalmente smascherato - Herrera, Rémy; Long, Zhiming; Feng, Zhixuan; Li, Bangxi (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2020)
The large US trade deficit vis-à-vis China was the main pretext used by Washington to trigger, starting from the first half of 2018, what is usually called a "trade war" against Beijing. Beyond the allegations of intellectual property theft and other courtesies, the reasons invoked by the US administration refer to allegedly unfair competition from China. In this context, China is assumed to accumulate the benefits of higher exports through low wages and an undervalued national currency on the one hand and those of imports hampered by subsidies to domestic companies and heavy regulatory constraints that prevent access to its market. However, an empirical analysis shows that the reality is very different and that if anything, it is the United States that takes advantage of an unfair exchange. USA; China; Foreign Trade; Exchange Rate; Unequal Exchange.